Electromagnetic Transients in Compensated Power Lines- Revisited: New Approach and Case Studies - Mohamed M. Saied (International Journal of Electrical and Communication Engineering Technology, 2024)
This paper addresses the simulation of the electromagnetic transients developed in high voltage power lines, which are initiated by lightning discharges. The analysis can handle both individual and simultaneous series inductive and shunt capacitive compensation types. The sizes and locations of the compensating elements are included in the analysis. The derived Laplace s-domain mathematical model applies the concept of the ABCD transmission constants representing equivalent two-port networks. The resulting currents and voltages along the line will be functions of the location and the Laplace operator s. A Mathematica code based on the Hosono algorithm is used for the numerical inversion of these expressions in order to get the corresponding results in the time domain. The model and computer code are validated via discussing the results of case studies with available solutions.
Keywords: Compensation; Simulation; electromagnetic; high voltage lines; mathematica; numerical Laplace inversion. Hooson algorithm; parallel; parameter study; series; transients